APPLICATION OF PROBLEM BASED LEARNING MODEL TO IMPROVE ACTIVITIES AND STUDENT LEARNING OUTCOMES OF CLASS XI IPA2 OF SMA NEGERI 5 TIDORE ON COLLOIDAL MATERIAL - Tamrin Taher (International Journal of Education, Information Technology, and Others, 2019)
This research is a classroom action research (CAR) that aims to improve the activities and learning outcomes of students on colloidal material at SMA Negeri 5 Tidore Kepulauan through the application of theModel Problem Based Learning. The subjects of this research are students class XI IPA2 SMA Negeri 5 Tidore Kepulauan even semester 2017/2018 school year totaling 23 people. The implementation of this research consisted of two cycles. The results showed that the application of themodel was Problem Based Learning effective in increasing the activities and learning outcomes of students especially for colloidal material. The increase was seen from (1) the average learning outcomes of students who completed in the first cycle of 52.17% to 82.60% in the second cycle. (2) Student activity shows an increase in asking, answer, and respond to the discussion activities from 65.22% in the first cycle to 78.26% in the second cycle.